1996
DOI: 10.1136/ard.55.7.442
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of apoptosis and expression of apoptosis related proteins in the synovium of patients with rheumatoid arthritis.

Abstract: Objectives-To investigate whether apoptosis occurs in the synovium of rheumatoid arthritis (RA), and the intermediate molecules operating in this process. Methods-DNA fragmentation was detected by in situ nick end labelling (ISNEL) in the synovium ofpatients with RA (n = 11) and control patients with femoral neck fracture (n = 5). The expression of proteins p53, p21WAF1/CIP1, c-myc, proliferating cell nuclear antigen (PCNA), and Bcl-2 was also examined by immunohistochemistry. Results-ISNEL positive synovial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
1
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 34 publications
(5 reference statements)
4
56
1
1
Order By: Relevance
“…Here, we demonstrated by immunohistochemistry that Bcl-2 was highly expressed in RA compared with OA ST. Dual immunofluorescence showed that although macrophages were variably positive, the majority of the Bcl-2-positive cells in the synovial lining and the sublining region were CD68-negative, synovial fibroblasts. In contrast, other studies revealed little Bcl-2 expression in the synovial lining (38) or sublining (40). The observed differences between these investigations and ours may have been technical.…”
Section: Discussioncontrasting
confidence: 55%
“…Here, we demonstrated by immunohistochemistry that Bcl-2 was highly expressed in RA compared with OA ST. Dual immunofluorescence showed that although macrophages were variably positive, the majority of the Bcl-2-positive cells in the synovial lining and the sublining region were CD68-negative, synovial fibroblasts. In contrast, other studies revealed little Bcl-2 expression in the synovial lining (38) or sublining (40). The observed differences between these investigations and ours may have been technical.…”
Section: Discussioncontrasting
confidence: 55%
“…So far, the question of whether alterations in the expression of c-Myc contribute specifically to the activation and invasiveness of RASFs (5) has not been investigated. Instead, there have been conflicting data, some of which have suggested a contribution of c-Myc to synovial proliferation (30), while others have pointed to apoptosis (51) or indicated no specific role of c-Myc in RA (52,53). Although c-myc mRNA does not appear to be increased in RASFs, c-Myc protein has been detected at sites of destruction (40).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms that contribute to the persistence of chronic inflammation observed in RA are poorly characterized; however, regulation of the proliferation of synovial fibroblasts and their resistance to apoptosis may be crucial in the pathogenesis of this disease (2). Histological evidence of apoptosis has not been observed in RA synovial tissue examined by electron microscopy (3,4). Joint inflammation and destruction in a variety of animal models, including streptococcal cell wall-induced arthritis, collagen-induced arthritis, the human T cell leukemia virus 1 tax transgenic model, and RA explants in SCID mice, have each been ameliorated by enhanced apoptosis (5)(6)(7), suggesting that increased apoptosis may be associated with an improved clinical outcome.…”
Section: R Heumatoid Arthritis (Ra)mentioning
confidence: 99%